Capabilities for advanced services: A multi-actor perspective - Story, Vicky M.; Raddats, Chris; Burton, Jamie; Zolkiewski, Judy; Baines, Tim (Industrial marketing management, 2017)
Servitization involves manufacturers developing service offerings to grow revenue and profit. Advanced services, in particular, can facilitate a more service-focused organization and impact customers' business processes significantly. However, approaches to servitization are often discussed solely from the manufacturer's perspective; overlooking the role of other network actors. Adopting a multi-actor perspective, this study investigates manufacturer, intermediary and customer perspectives to identify complementary and competing capabilities within a manufacturer's downstream network, required for advanced services. Interviews were conducted with 24 senior executives in 19 UK-based manufacturers, intermediaries and customers across multiple sectors. The study identified six key business activities, within which advanced services capabilities were grouped. The unique and critical capabilities for advanced services for each actor were identified as follows: manufacturers; the need to balance product and service innovation, developing customer-focused through-life service methodologies and having distinct, yet synergistic product and service cultures; intermediaries, the coordination and integration of third party products/services; customers, co-creating innovation and having processes supporting service outsourcing. The study is unique in highlighting the distinct roles of different actors in the provision of advanced services and shows that they can only be developed and delivered by the combination of complex interconnected capabilities found within a network. •We explore the capabilities required for advanced services from the perspectives of three actors; manufacturers, intermediaries and customers.•Within six key business activities, competitive (manufacturer, intermediary) and complementary (customer) capabilities are identified, six of which are unique and critical for advanced services.•For manufacturers, these unique and critical capabilities are: the need to balance product and service innovation, developing customer-focused through-life service methodologies and having distinct, yet synergistic product and service cultures.•For intermediaries, a unique and critical capability is the coordination and integration of third party products/services.•For customers, these capabilities are: co-creating innovation and having processes supporting service outsourcing.